A aplicação da análise de séries temporais (time series analysis) no estudo da dinâmica hidrológicas dos sistemas cársicos. Primeiros resultados para o maciço de Sicó (litoral-centro de Portugal) - Paiva, Isabel (2012)
The present study aims to know the hydrological dynamic of karst massif of Sicó (centre of Portugal). Furthermore, this paper demonstrates that time series analyses (correlation and spectral analysis) can contribute highly to understand the hydrodynamic behaviour of karst aquifers and deduce physical characteristics of the system (degree of karstification, storage capacity). The available data consists of 2 springs flow rates (Olhos d’Água do Anços and Ourão) and the precipitation for 2 hydrological years (2009/2010 and 2010/2011). The application of univariate (autocorrelation and spectral analysis) and bivariate analysis (cross-correlation, cross-amplitude, coherence, gain and phase functions) shows a bimodal hydrodynamic behaviour of this karst system. The results demonstrate a fast response to input signal suggesting a developed and well-organized conduit network which quickly drains the aquifer (predominance of quickflow). On the other hand, the long impulse response indicates the strong memory of the system, which hardly filters and attenuates the signal of precipitation. The dominant influence of baseflow on the spring discharge shows the large storage capacity of the karst system.